Comparison of anterior and posterior approaches for functional improvement in cervical myelopathy: A systematic review and meta-analysis of 33,025 patients - Abdulsalam Aleid, MD; Saud Aldanyowi, MD; Hasan Alaidarous, MD; Zainab Aleid, MD; Abdulaziz Alharthi, MD; Abbas Al Mutair, MD (North American Spine Society Journal)
ABSTRACT: Background: Cervical myelopathy is caused by pressure on the spinal cord in the neck, leading to pain, numbness, and balance issues. Surgery aims to decompress the spinal cord, with different approaches; anterior, posterior, or both depending on specifies. This systematic review and meta-analysis aimed to compare the risks and benefits of anterior and posterior surgical techniques. Methods: Adhering to the PRISMA guidelines, we conducted a systematic search across the databases including PubMed, Scopus, and Web of Science for studies comparing anterior and posterior surgical approaches for cervical myelopathy. Studies that met our predefined inclusion criteria were selected by 2 independent reviewers. The methodological quality of the selected studies was assessed using NOS and Rob-2 tools and analysis was done using the Review Manager tool. One RCT and 22 cohort studies including 33,025 patients were included in the analysis. Results: The anterior approach was associated with better neurological recovery and a greater improvement in Cobb's angle with MD of 4.18 (95%CI: 0.38, 7.91, p=.03), and 6.91 (95%CI: 1.85, 11.97, p=.007), respectively. The anterior approach showed a statistically significant decrease in VAS, and NDI scales with MD of −0.44 (95%CI: −0.75, −0.12, p=.007), and −1.91 (95%CI: −3.74, −0.09, p=.04), respectively as compared to posterior approach. Conclusions: Studies suggest that an anterior approach for cervical myelopathy may improve nerve function, correct spinal curvature more effectively, and lead to fewer complications, less pain, reduced blood loss, and a shorter hospital stay compared to a posterior approach.